Posisi Strategis Pendidikan Tinggi Dalam Pembangunan Ekonomi - Agustuti Handayani (PUBLICA, 2012)
Theory development in the past embraces the principle that poverty occurs because of a lack of ability to save and build physical capital. However, the theory was later corrected by another theory which states that